(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2016)
The Naskapi Nation of Kawawachikamach is an Aboriginal community located in northern Quebec near the Labrador Border. Given the region’s rich iron deposits, the Naskapi Nation has considerable experience with major mineral development, first in the 1950s to the 1980s, and again in the past decade as companies implement plans for further extraction. This has raised concerns regarding a range of environmental and socio-economic impacts that may be caused by renewed development. These concerns have led to an interest among the Naskapi to develop a means to track community well-being over time using indicators of their own design. Exemplifying community-engaged research, this paper describes the beginning development of such a tool in fall 2012—the creation of a baseline of community well-being against which mining-induced change can be identified. Its development owes much to the remarkable and sustained contribution of many key members of the Naskapi Nation. If on-going surveying is completed based on the chosen indicators, the Nation will be better positioned to recognize shifts in its well-being and to communicate these shifts to its partners. In addition, long-term monitoring will allow the Naskapi Nation to contribute to more universal understanding of the impacts of mining for Indigenous peoples.